Non-autoimmune subclinical hypothyroidism due to a mutation in TSH receptor: report on two brothers - Cerbone Manuela; Agretti Patrizia; De Marco Giuseppina; Improda Nicola; Pignata Claudio; Santamaria Francesca; Tonacchera Massimo; Salerno Mariacarolina (BMC, 2013)
Abstract Subclinical hypothyroidism (SH) is a condition characterized by a mild persistent thyroid failure. The main cause is represented by autoimmune thyroiditis, but mutations in genes encoding proteins involved in TSH pathway are thought to be responsible for SH, particularly in cases arising in familial settings. Patients with the syndrome of TSH unresponsiveness may have compensated or overt hypothyroidism with a wide spectrum of clinical and morphological alterations depending on the degree of impairment of TSH-receptor (TSH-R) function. We describe the case of two brothers with non autoimmune SH carrying the same heterozygous mutation in the extracellular domain of TSH-R and presenting with different clinical, biochemical and morphological features. The first one had only a slight persistent elevation of TSH, a normal thyroid ultrasound and did never require l- thyroxine (L-T4) replacement treatment. The second one had a neonatal persistent moderate TSH levels increase associated with a thyroid gland hypoplasia and was treated with L-T4 since the first months of life. These two cases support the recent association of TSH-R mutations inheritance as an autosomal dominant pattern with variable expressivity and suggest that the decision to start replacement therapy in patients with persistent SH due to TSH resistance should be individualized.